Optimalisasi Partisipasi Masyarakat dalam Penganggaran : Strategi dan Rekomendasi Kebijakan - Nurakhmadi, Dito Arief; Rahmawan, Triya Indra; Suhendro, Saring (Peradaban Journal of Law and Society, 2024)
Community participation in budgeting is a crucial element in maintaining transparency and accountability in regional financial management. Based on Government Regulation of the Republic of Indonesia Number 45 of 2017 concerning Community Participation in Local Governance, regional governments are required to encourage public involvement in the process of formulating general budget policies for regional revenue and expenditure as well as temporary budget priorities and ceilings. This participatory process involves gathering input from the community through various methods such as surveys, community meetings, or online platforms. Despite the existing regulations, there are challenges in implementation, including a lack of public understanding of public budgets and bureaucratic resistance. Legal aspects also play a significant role in either encouraging or hindering community participation. This study aims to analyze the legal framework governing community participation in the budgeting process in Indonesia, identify the legal obstacles faced, and provide policy recommendations to enhance community participation. By implementing recommendations such as the use of e-Participatory Budgeting (e-PB) and participatory design, it is expected that community participation in the budgeting process will increase, resulting in public policies that are more responsive to the needs and aspirations of the community, and strengthening accountability and transparency in governance. Partisipasi masyarakat dalam penganggaran merupakan elemen krusial dalam menjaga transparansi dan akuntabilitas pengelolaan keuangan daerah. Berdasarkan Peraturan Pemerintah Republik Indonesia Nomor 45 Tahun 2017 tentang Partisipasi Masyarakat dalam Penyelenggaraan Pemerintahan Daerah, pemerintah daerah diwajibkan mendorong keterlibatan masyarakat dalam proses penyusunan kebijakan umum anggaran pendapatan dan belanja daerah serta prioritas dan plafon anggaran sementara. Proses partisipasi ini melibatkan pengumpulan masukan dari masyarakat melalui berbagai metode seperti survei, pertemuan komunitas, atau platform online. Meskipun regulasi telah ada, terdapat tantangan dalam implementasi, termasuk kurangnya pemahaman masyarakat tentang anggaran publik dan resistensi birokrasi. Aspek hukum juga berperan penting dalam mendorong atau menghambat partisipasi masyarakat. Kajian ini bertujuan untuk menganalisis kerangka hukum yang mengatur partisipasi masyarakat dalam proses penganggaran di Indonesia, mengidentifikasi kendala hukum yang dihadapi, dan memberikan rekomendasi kebijakan untuk meningkatkan partisipasi masyarakat. Melalui penerapan rekomendasi seperti penggunaan e-Participatory Budgeting (e-PB) dan desain perancangan partisipatif, diharapkan partisipasi masyarakat dalam proses penganggaran dapat meningkat, sehingga kebijakan publik yang dihasilkan lebih responsif terhadap kebutuhan dan aspirasi masyarakat, serta memperkuat akuntabilitas dan transparansi dalam pemerintahan.